Assessment of climate change in Europe from an ensemble of regional climate models by the use of Köppen–Trewartha classification. (11th September 2012) - Gallardo, Clemente; Gil, Victoria; Hagel, Edit; Tejeda, César; de Castro, Manuel
ABSTRACT Through the use of the climatic classification of Köppen–Trewartha (K‐T), the ability to reproduce the current climate of Europe has been shown for an ensemble of 15 regional climate model simulations nested in six global climate models. Depending on the simulation, between 55.4 and 81.3% of the grid points are in agreement with observations regarding the location of climate types in current climate simulations (1971–2000). In this respect, the result of the ensemble of 15 simulations is better than that of any individual model, with 83.5% of the grid points in agreement with observations. K‐T classification has also been used to analyse the projected climate change over the 21st century under the SRES‐A1B emissions scenario. It was found that 22.3% of the grid points in the domain change their climate by the period 2021–2050 compared to current climate and 48.1% change by 2061–2090. The climate shifts affecting the biggest extensions are projected in Central Europe and Fennoscandia, but other smaller areas suffer more intense changes which potentially are more dangerous to vegetation and ecosystems. Generally, these changes occur at a sustained rate throughout the century, reaching speeds of up to 90 × 103 km2 decade−1 in the retreat or expansion of some climates.